2021
DOI: 10.1038/s41413-020-00122-0
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin signalling in bone homeostasis, with age and in disease

Abstract: Adiponectin is the most abundant circulating adipokine and is primarily involved in glucose metabolism and insulin resistance. Within the bone, osteoblasts and osteoclasts express the adiponectin receptors, however, there are conflicting reports on the effects of adiponectin on bone formation and turnover. Many studies have shown a pro-osteogenic role for adiponectin in in vivo murine models and in vitro: with increased osteoblast differentiation and activity, alongside lower levels of osteoclastogenesis. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 116 publications
(180 reference statements)
0
37
1
1
Order By: Relevance
“…bm SF has recently attracted attention for biomacromolecule delivery due to its stabilizing effect on sensitive biological compounds (e.g. antibiotics) [ 24 ] and its hypoallergenicity [ 25 , 26 ]. However, bm SF molecules do not contain cell recognition motifs, such as arginylglycylaspartic acid (RGD), which facilitates cell adhesion and spreading.…”
Section: Introductionmentioning
confidence: 99%
“…bm SF has recently attracted attention for biomacromolecule delivery due to its stabilizing effect on sensitive biological compounds (e.g. antibiotics) [ 24 ] and its hypoallergenicity [ 25 , 26 ]. However, bm SF molecules do not contain cell recognition motifs, such as arginylglycylaspartic acid (RGD), which facilitates cell adhesion and spreading.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin receptor 2 (ADIPOR2) is a member of the adipocytokines gene family. Generally, adiponectin receptor genes play an important role in bone and whole-body energy homeostasis that could be induced by activation of the AMPK signaling pathway; ADIPOR1 and ADIPOR2 also play a crucial role in metabolic pathways, which lead to the regulation of lipid and glucose metabolism, oxidative stress and inflammation [49]. Ouyang et al [50] reported ADIPOR2 has a role in intramuscular fat content in the longissimus dorsi (LD) muscle of different pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al [50] reported ADIPOR2 has a role in intramuscular fat content in the longissimus dorsi (LD) muscle of different pig breeds. Lewis et al [49] discussed in detail the role of adiponectin signaling in bone homeostasis and its effect on the lifestyle of human healthy aging and disease. Moreover, ADIPOR2 is considered to be one of the genes associated with conformation and reproductive performance traits (hip height, rump length, calving ease, height, ovulation, type and rump angle) in one of the South African cattle breeds [51].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix (ECM) bone mainly comprises of 0–70% primarily inorganic hydroxyapatite (HAp), 20–40% organic constituents (primarily type I collagen), 5–10% water, and 3% lipid and proteins such as growth factors [ 25 ]. Conventional bone treatment methods, including autografts, allografts, and xenografts, are restricted due to their potential infection, risks of donor-site morbidity, high nonunion rate with host tissues, and adverse immune response [ 58 ].…”
Section: Tissue Engineering Applications and Cancer Drug Deliverymentioning
confidence: 99%
“…The structure of intelligent hydrogels can be altered by different types of stimuli from internal (e.g., in-body) or external (i.e., out-body) sources. Internal and external sources are classified as biological, physical, and chemical [ 25 ].…”
Section: Introductionmentioning
confidence: 99%